A New Algorithm for Computing the Inverse and Generalized Inverse of the Scaled Factor Circulant Matrix (Journal of Computational Mathematics, 2018)
A new algorithm for finding the inverse of a nonsingular scaled factor circulant matrix is presented by the Euclid's algorithm. Extension is made to compute the group inverse and the Moore-Penrose inverse of the singular scaled factor circulant matrix. Numerical examples are presented to demonstrate the implementation of the proposed algorithm.
Keywords: Scaled factor circulant matrix; Inverse; Group inverse; Moore-Penrose inverse.